2015
DOI: 10.20884/1.anprod.2015.17.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Methane Gas Reduction Using Virgin Coconut Oil Supplementation in Rumen Fermentation through in Vitro

Abstract: Abstract. This study aims to determine the effect of virgin coconut oil (VCO)supplementation in ruminant feed on the methane reduction in vitro. The study used rumen fluid with forage substrate and concentrates in the ratio of 60:40. The experiement consists of five kinds of VCO treatments, namely: R0 -feed substrates without VCO; R1 -feed substrates with 2% VCO; R2 -feed substrates with 4% VCO; R3 -feed substrates with 6% VCO; and R4 -feed substrates with 8% VCO. Each treatment was done three times. The ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
0
8
0
1
Order By: Relevance
“…Hydrogenation of double bonds in unsaturated fatty acids produced hydrogens that were used for saturated fatty acid formation. However, hydrogens were not only used for saturated fatty acid formation, but also for producing methane gas by methanogenic bacteria and for propionate production by propionic bacteria (Sondakh et al, 2015). This may cause a competition for hydrogen utilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogenation of double bonds in unsaturated fatty acids produced hydrogens that were used for saturated fatty acid formation. However, hydrogens were not only used for saturated fatty acid formation, but also for producing methane gas by methanogenic bacteria and for propionate production by propionic bacteria (Sondakh et al, 2015). This may cause a competition for hydrogen utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In their symbiosis, the protozoa released the hydrogen which were then transferred to the methanogenic bacteria to produce methane. To reduce methane production needs to inhibit growth of protozoa (Machmuller, 2006;Bhatta et al, 2013;Sondakh et al, 2015). However, several researchers indicated that reduction of methane production through protozoal defaunation caused some problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of methane can also occur when cattle are given feed containing medium chain fatty acids (MCFA) and there has been a study conducted by Machmuller (2006) using canola oil. Sondakh et al (2015) conducted a research on reducing of methane using virgin coconut oil as a medium chain fatty acids source, in which the results of such research could decrease methane and increase propionic acid in rumen fluid fermentation in vitro. Medium chain fatty acids are fatty acids that function as defaunation agents (Sondakh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Medium chain fatty acids are fatty acids that function as defaunation agents (Sondakh et al, 2012). Research of Machmuller (2006) and Sondakh et al (2015) using canola oil and VCO was very expensive and it will be difficult for further applications.…”
Section: Introductionmentioning
confidence: 99%